Adhesive capsulitis in a patient affected by KBG Syndrome - Vigni, Giulio Edoardo; Tomasi, Andrea; Sabbioni, Giacomo; Fazzari, Federico; Surace, Michele Francesco; Camarda, Lawrence; Gervasi, Enrico (Acta Biomedica Atenei Parmensis, 2021)
Background and Case presentationKBG syndrome is a multiple congenital anomaly syndrome with variable presentation. Many physical anomalies also affect the orthopaedic field. We present a case of a young woman with diagnosis of KBG syndrome that is also affected by joint stiffness and adhesive capsulitis to the shoulders.DiscussionMany other cases have been reported to present joint stiffness and formation of keloids. Adhesive capsulitis is known to be related to autoimmune pathologies and endocrinological disorders. KBG syndrome is caused by heterozygous mutation in ANKRD11 gene and few patients with hypermobility of the joints have also been reported.ConclusionsThe KBG syndrome might present a risk factor for adhesive capsulitis of the shoulder and joint stiffness in general. Moreover, the tendency to the formation of keloids and sporadic cases of hypermobility might suggest a connective tissue involvement in different gene deletions.